Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Seagrass Organic Carbon Stocks Show Minimal Variation Over Short Time Scales in a Heterogeneous Subtropical Seascape - Jimena Samper-Villarreal; Peter J. Mumby; Megan I. Saunders; Chris Roelfsema; Catherine E. Lovelock (Estuaries and Coasts, 2018)

Freedom from Tritrichomonas foetus infection in cattle in St. Kitts - Kimberly E. Coker; Joseph J. Lim; Rebecca L. Schleisman; Christopher Vosloo; Hilari M. French; Juan C. Samper; John J. Callanan; Robert O. Gilbert; Fortune Sithole; Chaoqun Yao; Aspinas Chapwanya (Tropical Animal Health and Production, 2018)

Using eDNA to determine the source of organic carbon in seagrass meadows - Ruth Reef; Trisha B. Atwood; Jimena Samper‐Villarreal; Maria Fernanda Adame; Eugenia M. Sampayo; Catherine E. Lovelock (Limnology and Oceanography, 2017)
Seagrasses sequester globally significant amounts of carbon (C), which is stored mainly in the sediment. Both C fixation by the seagrass (autochthonous) and the trapping of organic matter that is derived from outside the ecosystem (allochthonous) contribute to seagrass sediment organic C (OC). However, due to limitations in current methods we do not yet fully understand which sources of C are most important to blue C ecosystems. We used environmental‐DNA (eDNA) to identify and estimate the contribution of floral sources to seagrass sediment OC sampled from three sites in Moreton Bay, Australia that differ in potential levels of autochthonous and allochthonous OC inputs. Using the plant barcode gene rbcL and a next‐generation sequencing platform we identified 150 plant operational taxonomic units in the sediment samples. We found that seagrass DNA composed on average 88% of the eDNA pool in the sediment samples. Allochtonous sources were primarily mangrove, saltmarsh, and freshwater marsh species, but the proportional contribution of other sources varied among meadows. Carbon and nitrogen (N) stable isotope mixing models suggested a lower autochthonous contribution than the eDNA data, but had high ambiguity due to indistinguishable isotopic values among some of the sources. Our study shows that eDNA can be an effective tool for identifying sources to sediment OC in blue C ecosystems and can be used in conjunction with stable isotope analysis to reduce ambiguity. Identifying the sources of OC to the sediments of blue C ecosystems is crucial for building robust and accurate C budgets for these systems.

Organic carbon in seagrass sediments is influenced by seagrass canopy complexity, turbidity, wave height, and water depth - Jimena Samper‐Villarreal; Catherine E. Lovelock; Megan I. Saunders; Chris Roelfsema; Peter J. Mumby (Limnology and Oceanography, 2016)
Seagrass meadows are important marine carbon sinks, yet they are threatened and declining worldwide. Seagrass management and conservation requires adequate understanding of the physical and biological factors determining carbon content in seagrass sediments. Here, we identified key factors that influence carbon content in seagrass meadows across several environmental gradients in Moreton Bay, SE Queensland. Sampling was conducted in two regions: (1) Canopy Complexity , 98 sites on the Eastern Banks, where seagrass canopy structure and species composition varied while turbidity was consistently low; and (2) Turbidity Gradient , 11 locations across the entire bay, where turbidity varied among sampling locations. Sediment organic carbon content and seagrass structural complexity (shoot density, leaf area, and species specific characteristics) were measured from shallow sediment and seagrass biomass cores at each location, respectively. Environmental data were obtained from empirical measurements (water quality) and models (wave height). The key factors influencing carbon content in seagrass sediments were seagrass structural complexity, turbidity, water depth, and wave height. In the Canopy Complexity region, carbon content was higher for shallower sites and those with higher seagrass structural complexity. When turbidity varied along the Turbidity Gradient , carbon content was higher at sites with high turbidity. In both regions carbon content was consistently higher in sheltered areas with lower wave height. Seagrass canopy structure, water depth, turbidity, and hydrodynamic setting of seagrass meadows should therefore be considered in conservation and management strategies that aim to maximize sediment carbon content.

Conceptualizing a mountain hydrogeologic system by using an integrated groundwater assessment (Serra da Estrela, Central Portugal): a review - Jorge Espinha Marques; José M. Marques; Helder I. Chaminé; Paula M. Carreira; Paulo E. Fonseca; Fernando A. Monteiro Santos; Rui Moura; Javier Samper; Bruno Pisani; José Teixeira; José Martins Carvalho; Fernando Rocha; et al. (Geosciences Journal, 2013)

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Evaluation of alternative nitrogen and carbon sources for sugarbeet suspension culture platings in development of cell selection schemes - J. W. Saunders; C. J. Tsai; E. Samper (In Vitro Cellular & Developmental Biology - Plant, 1997)